Need analysis as the foundation to develop supplementary material for tenth grade students - Tri Mulyaningsih; Yohanes Gatot Sutapa Yuliana (Journal of English Language Teaching Innovations and Materials (Jeltim), 2019)
This research used a descriptive method to explore the needs of tenth grade students in learning English writing. In order to achieve this purpose, classroom observation, questionnaire, and interview were conducted to collect the data. In addition, several related documents such as 2013 curriculum, syllabus, the current English textbook used were analyzed. The results showed that the students are in intermediate level. Moreover, they had difficulties to write in correct grammar. Furthermore, there was also a need to provide the topics related to art and culture and daily life in the language material. Malay culture became the choice of the students to be the theme of their learning material. Moreover, the learning material needed to be completed with the teacher’s book which could give guidance to the teacher about the instruction or method that could be used in the classroom. Finally, the findings would be used as the base for developing the English writing material.